Impact of androgen suppression and zoledronic acid on bone mineral density and fractures in the Trans‐Tasman Radiation Oncology Group (TROG) 03.04 Randomised Androgen Deprivation and Radiotherapy (RADAR) randomized controlled trial for locally advanced prostate cancer. (11th February 2014) - Denham, James W.; Nowitz, Michael; Joseph, David; Duchesne, Gillian; Spry, Nigel A.; Lamb, David S.; Matthews, John; Turner, Sandra; Atkinson, Chris; Tai, Keen‐Hun; Gogna, Nirdosh Kumar; Kenny, Lizbeth; et al.
<x xml:space="preserve">Abstract</x> Objective To study the influence of adjuvant androgen suppression and bisphosphonates on incident vertebral and non‐spinal fracture rates and bone mineral density (BMD) in men with locally advanced prostate cancer. Patients and Methods Between 2003 and 2007, 1071 men with locally advanced prostate cancer were randomly allocated, using a 2 × 2 trial design, to 6 months i.m. leuprorelin (androgen suppression [AS]) before radiotherapy alone ± 12 months additional leuprorelin ± 18 months zoledronic acid (ZdA), commencing at randomization. The main endpoint was incident thoraco‐lumbar vertebral fractures, which were assessed radiographically at randomization and at 3 years, then reassessed by centralized review. Subsidiary endpoints included incident non‐spinal fractures, which were documented throughout follow‐up, and BMD, which was measured in 222 subjects at baseline, 2 years and 4 years. Results Incident vertebral fractures at 3 years were observed in 132 subjects. Their occurrence was not increased by 18 months' AS, nor reduced by ZdA. Incident non‐spinal fractures occurred in 72 subjects and were significantly related to AS duration but not to ZdA. Osteopenia and osteoporosis prevalence rates at baseline were 23.4 and 1.4%, respectively, at the hip. Treatment for 6 and 18 months with AS caused significant reductions in hip BMD at 2 and 4 years (P < 0.01) and ZdA prevented these losses at both time points. Conclusion In an AS‐naïve population, 18 months of ZdA treatment prevented the sustained BMD losses caused by 18 months of AS treatment; however, the study power was insufficient to show that AS duration or ZdA influenced vertebral fracture rates.